Forward Chaining Method for Diagnosing Diseases and Pests in Melon Plants - Dapiokta, Jum; Nurdiansyah, Rizky; Muris, Anggeraeni Agustin; Kuswanto, Joko (Universitas Pendidikan Nasional, 2024)
There are many problems encountered in the field of agriculture, for example problems about diseases and pests in melon plants. Experts or experts in the field of agriculture rarely need to build a system that is able to adopt human processes and ways of thinking in the form of an expert system. The purpose of this study is to build an expert system to diagnose diseases and pests in melon plants using the forward chaining method. A reasoning that starts from facts first to test the correctness of a hypothesis. The system was tested using the black box testing method which was tested on experts and melon farmers. Based on the results of testing using the black box testing method tested on experts and farmers, the results of the assessment were obtained that the expert system for diagnosing diseases in melon plants was proven to run well as expected with 100% validation. The end result of this expert system is to make it easier for users to carry out the consultation process by providing a list of indication of diseases and pests experienced. Then the control of the type of disease and pest will be displayed according to the selected indication. In addition, this expert system also makes it easier for admins to update data such as disease data, indication and control. This expert system application program is also not only beneficial for experts but can also be useful for farmers that ordinary people who do not understand a little about melon plant diseases and pests.